Pengaruh Kemampuan Berpikir Ilmiah dalam Pembelajaran Inkuiri Terbimbing terhadap Hasil Belajar Siswa - Trining Puji Astutik (Universitas Pendidikan Mandalika Mataram, 2021)
To understand microscopic representation, scientific reasoning skill (SRS) is required. Unfortunately, some research has reported that many senior high school students have not developed formal thinking ability which is necessary to support the development of SRS. Research results reported that guided inquiry is a mode of learning effective in developing students’ formal thinking ability. Therefore, guided inquiry is also expected effective in developing SRS.This study, thus, aimed to identifythe effect of students’ scientific reasoning skill on their achievement. Participants were selected from two classes of grade X Science and Math students at SMA Laboratorium UM. They were matched based on their scientific reasoning skill test score. Two similar groups were obtained where each group consisted of 6 students with concrete level, 6 students with low formal level, and 4 students with upper formal level. A group of students were taught using guided inquiry learning. Data collected was the students’ score on scientific reasoning skill (SRS). The reliability of Bahasa Indonesia version test measured was 0,74. The data was analyzed using ANOVA. The results of this study showed that the students who were at the upper formal level of SRS had better achievement than those who were at the low formal and concrete level of SRS.